2022
DOI: 10.1007/s00394-022-02829-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a natural polyphenol supplement on iron absorption in adults with hereditary hemochromatosis

Abstract: Objectives We developed a natural polyphenol supplement that strongly chelates iron in vitro and assessed its effect on non-heme iron absorption in patients with hereditary hemochromatosis (HH). Methods We performed in vitro iron digestion experiments to determine iron precipitation by 12 polyphenol-rich dietary sources, and formulated a polyphenol supplement (PPS) containing black tea powder, cocoa powder and grape juice extract. In a multi-center, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…In addition, polyphenols could also reverse organ damage caused by (Buerkli et al, 2022); in this way, more attention is in need to understand the inhibiting iron absorption effects of polyphenols.…”
Section: Hemochromatosismentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, polyphenols could also reverse organ damage caused by (Buerkli et al, 2022); in this way, more attention is in need to understand the inhibiting iron absorption effects of polyphenols.…”
Section: Hemochromatosismentioning
confidence: 99%
“…(2020) compared the alleviation effects of procyanidins on dietary iron absorption in patients and mice, and they found that the procyanidin supplementation showed unremarkable protections on either type I HH or dysmetabolic iron overload syndrome in murine models, which was quite inconsistent with the results in human. Buerkli et al., 2022 formulated a polyphenol supplement (PPS) containing black tea powder, cocoa powder, and grape juice extract and performed iron digestion experiments to assess its effect on nonheme iron absorption in patients with HH. Results indicated that natural PPS could decrease dietary iron absorption when taken with meals, and thereby reducing body iron accumulation and the frequency of phlebotomy in patients with HH (Buerkli et al., 2022); in this way, more attention is in need to understand the inhibiting iron absorption effects of polyphenols.…”
Section: Polyphenols Regulate Iron For Health Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with interval phlebotomy is most effective for reducing iron burden [1]. Dietary modification is not emphasized due to the lack of large clinical trials since HH is a rare condition but limiting iron intake is promising and can lead to a reduced phlebotomy requirement up to 1.5 liters per year [4,5,6 ▪ ]. This article aims to provide dietary guidelines for HH patients stemming from physiological concepts of iron absorption, animal studies, and limited patient studies…”
Section: Introductionmentioning
confidence: 99%